The Effects of Intensification on Rural Teachers’ Work - Gloria Penrice (New Zealand Journal of Teachers' Work)
This article reports on a study exploring in-school intensification experiences identified by six experienced rural teachers as constraining their teaching practice. School organisational structures, school cultures, personal relationships within the school context, along with high self-imposed expectations can result in an increased workload and demands on teachers’ time. This study examined the differing responses these teachers employed in an attempt to counteract or minimise the effects of intensification. The findings suggest that one adverse consequence of intensification may be the lack of time for teachers to critically reflect on their own pedagogical practice, and on the broader historical, social and political implications underpinning current policies and practices inherent within the New Zealand educational context.